2013
DOI: 10.1371/journal.pone.0078542
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies to Prolong the In Vivo Life Span of Iron-Based Contrast Agents for MRI

Abstract: Superparamagnetic iron oxide (SPIO) and ultra small superparamagnetic iron oxide (USPIO) nanoparticles have been developed as magnetic resonance imaging (MRI) contrast agents. Iron oxide nanoparticles, that become superparamagnetic if the core particle diameter is ~ 30nm or less, present R1 and R2 relaxivities which are much higher than those of conventional paramagnetic gadolinium chelates. Generally, these magnetic particles are coated with biocompatible polymers that prevent the agglomeration of the colloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…For example the approach taken by Antonelli et al (Antonelli, Sfara, Battistelli, et al 2013; Antonelli, Sfara, Weber, et al 2016) of loading SPIO nanoparticles in red blood cells (RBCs). Antonelli et al were able to achieve a blood circulation half-life of 48 hours for Resovist loaded RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…For example the approach taken by Antonelli et al (Antonelli, Sfara, Battistelli, et al 2013; Antonelli, Sfara, Weber, et al 2016) of loading SPIO nanoparticles in red blood cells (RBCs). Antonelli et al were able to achieve a blood circulation half-life of 48 hours for Resovist loaded RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have suggested this method for the prolongation of SPIOs contrast agents life span in the blood circulation; optimally, this extends the blood retention time toward the half-life of RBCs, which is around 11 days in mice 128 and 30 days in humans. 129 Interestingly, in order to increase SPIO concentrations in animal blood circulation Antonelli et al 126 have developed a new procedure that involves the infusion of human SPIO-loaded RBCs in animal models, mice and rats. Before the infusion, the animals were treated with clodronate, a potent bisphosphonate (BP) generally used to inhibit osteoclastic bone resorption which is able to induce a reversible depletion of tissue macrophages.…”
Section: Rbcs For the Encapsulation And Delivery Of Magnetic Nanopartmentioning
confidence: 99%
“…The results showed how higher iron concentrations in animal bloodstream can be obtained using larger SPIO nanoparticle containers, such as human red blood cells, combined with a transient depletion of tissue macrophages induced by clodronate. 126 The improved in vivo SPIO life span could significantly aid MRI diagnosis in a clinical setting where delays can occur and also allows the RBCs to enter deep into body tissues. Indeed, the increased stability and viability of the SPIOloaded RBCs would allow the same patient to be imaged 134 have applied the loading procedure to a new contrast agent, the P904 ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles coated by hydrophilic derivatives of glucose, [135][136][137][138] developed by Guerbet Laboratories.…”
Section: Rbcs For the Encapsulation And Delivery Of Magnetic Nanopartmentioning
confidence: 99%
“…For these applications, nanoparticles can be encapsulated in PEGylated PRINT nanoparticles with circulation half-life of 19.5 hours 34 or in red blood cells with tracer life span in the mice bloodstream prolonged to 12 days. 35 …”
mentioning
confidence: 99%